Tendencias en procedimientos meniscales y reconstrucción de ligamentos de rodilla en Chile: estudio transversal entre 2004-2019 - Barahona V., Maximiliano; Palet B., Miguel; Zamorano C., Álvaro; Barahona V., Macarena; Infante C., Carlos; Hinzpeter C., Jaime (Revista Hospital Clínico Universidad de Chile, 2023)
Purpose: The aim of this study was to describe the incidence rate per 100,000 inhabitants (IR) of knee arthroscopic procedures and knee ligament reconstruction in Chile, between 2004 and 2019. Methods: Cross-sectional study. Patients who underwent a meniscal surgery and patients undergoing knee ligament reconstruction were identified in the database of the Chilean department of statistics and health information (DEIS) between 2004 and 2019. Results: The DEIS reported 149,734 patients, 169244 arthroscopic procedures with a significant upward trend in the IR, from 24.61 in 2004 to 80.6 in 2019. Related to knee ligament reconstruction, 42,026 procedures were found in 38,171 patients, with a significant upward trend in the IR, from 4.08 in 2004 to 24.62 in 2019. Conclusions: Knee arthroscopy and ligament reconstruction are in an upward trend in Chile. An evident inequity in access was found public insurance needs to improve the quality and access to both procedures. An updated, national registry is urgently needed to improve data, allowing better health policies.